Roselle Calyx Extract as an Antioxidant Supplement on Tris-Base Extender for Goat Semen - Nur Hafizah Mohammed; Mashitah ShikhMaidin; Christina Yong Seok Yien (UNIVERSITAS ISLAM LAMONGAN, 2022)
In this study, we used extract from Roselle (Hisbiscus sabdariffa L.) Calyx to determine its ability as an antioxidant supplement to improve motility, progressive score and abnormality of goat’s sperms. Pooled semen from four male goats with average of live body weight 34.4 ± 0.6 kg and body condition score 2.5 ± 0.1 were aliquot into two groups: Control group; 0 mg/ml and Treatment groups; (Treatment 1:13 mg/ml, Treatment 2: 20 mg/ml, Treatment 3: 33 mg/ml, Treatment 4: 43 mg/ml of Roselle’s extract. All the semen parameter was observed at 0 hour, 0.5 hour, 1.0 hour, 1.5 hours after semen collection. The supplementation of extender with 13 mg/ml, 20 mg/ml, 33 mg/ml, 43 mg/ml of extract from Roselle Calyx does not affect sperm motility, progressive score and morphology of goat (p>0.05). However, all sperm, regardless with supplementation and without supplementation of Roselle extract were maintained in good quality (60%) up to 1.5 hours. It is quite difficult to conclude that there are no effect of Roselle extract on sperm quality due to arise possibility of factors that may contribute to inefficiency effect of Roselle extract on sperm parameter. There were high possibility that the causes are due to inefficiencies of extraction method and/or degradation of anthocyanin pigment during extraction and storage process. Unsuitable extraction method could results in low yield and unstable of anthocyanin pigment. Moreover, temperature, pH and light causes the pigment to become unstable during processing and storage leading to degradation. Thus we suggest anthocyanin content monitoring in extract Roselle Calyx are required for future study.